A Comparison of Antimicrobial Resistance of XDR and MDR clinical isolates of E. coli, Klebsiella spp. & Pseudomonas spp. against Amikacin & Imipenem - Zuhair Ali Rizvi, Zuhair Ali Rizvi; Sundas abbas, Sundas abbas; Sana Khalid, Sana Khalid; Muhammad Ali, Muhammad Ali (Students’ Supplement of Journal of Rawalpindi Medical College, 2019)
Background: Increased antimicrobial resistance has led to increase in mortality and morbidity. Objective: To determine and compare antimicrobial resistance of Multi Drug Resistant (MDR) and Extensively Drug Resistant (XDR) clinical isolates of E. coli, Pseudomonas spp. & Klebsiella spp. against Amikacin and Imipenem in a tertiary care hospital. Methods: This descriptive cross-sectional study was carried out from July 2017 to July 2018 Department of Pathology, Holy Family Hospital, Rawalpindi. A total of 673 clinical isolates of E. coli, Klebsiella spp. and Pseudomonas spp. were included in this study by consecutive sampling technique. Data was entered in SPSS and descriptive statistics were applied. Chi’s square test was applied to determine difference in effectiveness of amikacin and imipenem against XDR and MDR strains of included micro-organisms. Results: A total of 673 samples were included in this study, out of which 431 (64.0%) strains of gram- negative XDR organisms isolated, 123 (55.9%) strains were of E. coli, 134 (68.4%) of Klebsiella and 174 (67.7%) strains were of Pseudomonas. A total of 366 (54.4%) were obtained from male and 307 (45.6%) from female patients. Pseudomonas (38.2%) was more commonly isolated as compared to E. coli (32.7%). Conclusion: Antimicrobial resistance of XDR isolates of E. coli, Klebsiella spp. & Pseudomonas spp. against Amikacin & Imipenem is high as compared to MDR clinical isolates.